(5x-2)-(-5x+4)=

Simple and best practice solution for (5x-2)-(-5x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-2)-(-5x+4)= equation:


Simplifying
(5x + -2) + -1(-5x + 4) = 0

Reorder the terms:
(-2 + 5x) + -1(-5x + 4) = 0

Remove parenthesis around (-2 + 5x)
-2 + 5x + -1(-5x + 4) = 0

Reorder the terms:
-2 + 5x + -1(4 + -5x) = 0
-2 + 5x + (4 * -1 + -5x * -1) = 0
-2 + 5x + (-4 + 5x) = 0

Reorder the terms:
-2 + -4 + 5x + 5x = 0

Combine like terms: -2 + -4 = -6
-6 + 5x + 5x = 0

Combine like terms: 5x + 5x = 10x
-6 + 10x = 0

Solving
-6 + 10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 10x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 10x = 0 + 6
10x = 0 + 6

Combine like terms: 0 + 6 = 6
10x = 6

Divide each side by '10'.
x = 0.6

Simplifying
x = 0.6

See similar equations:

| 0=x^4+8x^3+18x^2+8x+4 | | a/4-1/4=-5 | | 6+2x+2x=4x+x | | 1/4(-2+n) | | 4n/5-1/5 | | 8-4x=5-x | | F/7-(-14)=18 | | -5600+200t=-2800 | | 3.8T+22.8=11.4T+68.4 | | 5(n+2)3/5(5+10n) | | 3(3-m)=2(3m+3) | | 6+2a=3+7a | | (2x-2)+(x+5)=90 | | -5600+200t=2800 | | 4=4+4v | | x^2+8x-19=5x+1 | | 4x+2x+2x=4x+x | | 2t-(-12)=50 | | u^2-5u-36=0 | | k(x+2)=3(x+8) | | 4x+22=45-9x | | -5600+200t=50 | | 4-x=2-x/2 | | 7w-14w=-28 | | -5600+200t=0 | | 5z=14-44 | | 5+-2v=1 | | 2u^2+11u+12=0 | | x^2-13x+41=1 | | x/5+6=30 | | 3+4i/4-2i | | S/3+16=20 |

Equations solver categories